Evaluating the research capacity and culture amongst staff at a tertiary level teaching hospital in Rwanda. - Kara L Neil; Daniella Rangira; Edouard Ngendahayo; Natalie McCall; Rafiki M Gatera (PLoS ONE)
Background Building research capacity can strengthen health systems through evidence-based interventions. However, evaluating the current research capacity and increasing it is a layered process that needs to consider different institutional structures, as well as internal factors. This study collects baseline data on the research capacity and culture at King Faisal Hospital Rwanda (KFH), a tertiary-level teaching hospital in Rwanda. It also proposes ways to further strengthen it and recommends ways for other institutions in Rwanda to strengthen research capacity. Methods The Research Capacity and Culture Tool was distributed to full-time clinical and non-clinical KFH staff in September 2021. Participants were required to hold a position that minimally requires an Advanced Diploma. The quantitative survey data were analyzed in SPSS Version 27 and analyzed via descriptive statistics across all domains, including the individual, organizational, and team levels. Findings 152 participants completed the questionnaire. On a 5-point Likert scale, the highest ranked skills were designing questionnaires (3.34) and using digital referencing systems (3.29), while the lowest ranked skills were securing research funding (2.40) and writing for publication in peer-reviewed journals (2.46). Perceptions about the organizational level's research system were overall stronger than those at the team level, with the weakest team-level system being having regular research forums and bulletins (2.14) and having digital tools for conducting research (2.14). Motivators to conducting research included skills development (87%) and career advancement (74%), while barriers included a lack of time (64%) and access to funding (56%). Discussion To strengthen the research capacity and culture at KFH, focus should be on allocating tools, resources, and training opportunities to staff. Research should be integrated into staff job descriptions, with a time audit conducted to ensure they have adequate time for these activities. Finally, decentralizing research and ensuring team-level ownership will help with staff buy in.